L’opera di Tito Marrone all’interno del cenacolo romano di Sergio Corazzini - Comberiati, Daniele (Incontri. Rivista europea di studi italiani, 2012)
Tito Marrone’s Work Inside Sergio Corazzini’s Roman Club The poetic work of Tito Marrone, forgotten for years due to his prolonged creative silence, reveals itself to be key to understanding how the Crepuscolar Roman related to the Francophone Symbolist poets. Marrone, slightly more senior than his associates, was the only one to possess a solid grasp of French culture and command of its language. His association with Rosso di San Secondo and with Pirandello, additionally, shows an author needlessly excluded from the cultural context of the time: his presence as a character in Pirandello’s novel Suo marito and as a protagonist in Rosso di San Secondo’s Storie di uomini e di angeli is testimony to the bond he had with these two authors, who were, inter alia, his contemporaries. Moreover, Marrone was in contact with different proponents of Sicilian Futurism, and so Crepuscolar and Futurist influences also characterized his use of language and poetic style. Ultimately of interest are Marrone’s reviews and critical writing, that show a fine analytic eye and capacity to gather and interpret the authentic elements of his contemporary literary and theatrical milieu. And so, for these reasons, it would now be beneficial to shed light on and critically anthologize Marrone’s ample texts, which themselves would also come to be important in the Crepuscolar Roman movement.